Investigate tumour heterogeneity and genetic pathways in colorectal cancer - Ham Karim, Hersh Abdul (2017)
Background: Colorectal cancer is a major global public health problem that has predominantly been considered a genetic disease following a precise series of molecular events. These are characterized by sequential accumulation of genetic and epigenetic alteration in several oncogenes and tumour suppressor genes. Understanding of the genetic mechanisms that explain the initiation and evolution of colorectal cancer are key to improving risk prediction, prognostication and treatment.